The forbidden modern civilization and veiling - Göle, Nilüfer 1953- (Univ. of Michigan Press, 1996)
In The forbidden modern, prominent Turkish scholar Nilüfer Göle examines the complex relationships among modernity, religion, and gender relations in the Middle East. Her focus is on the factors that influence young women pursuing university educations in Turkey to adopt seemingly fundamentalist Islamist traditions, such as veiling, and the complex web of meanings attributed to these gender-separating practices. Veiling, a politicized practice that conceptually forces people to choose between the "modern" and the "backward," provides an insightful way of looking at the contemporary Islam-West conflict, shedding light on the recent rise of Islamist fundamentalism in many countries and providing insight into what is a more complex phenomenon than is commonly portrayed in accounts by Western journalists. Gole's sociological approach, employing a number of personal interviews, allows for both a detailed case study of these young Turkish women who are turning to the tenets of fundamental Islamist gender codes, and for a broader critique of Eurocentrism and the academic literature regarding the construction of meaning. Both perspectives serve as a springboard for the launching of theoretical innovations into feminist, religious, cultural, and area studies.
Keywords: Geschichte; Geschichte 1983-1994; Femmes - Turquie - Conditions sociales; Femmes dans l'islam - Turquie; Islam; Musulmanes - Morale pratique; Sluiers; Voiles (costume) - Turquie; Vrouwendiscriminatie; Frau; Islamic clothing and dress -- Turkey; Muslim women -- Turkey; Purdah -- Turkey; Veils -- Turkey; Women in Islam -- Turkey; Women -- Turkey -- Social conditions; Psychosoziale Situation; Schleier; Fundamentalismus; Feminismus; Laizismus; Reislamisierung; Soziale Situation; Islamisierung; Frauenemanzipation; Europäisierung; Muslimin; Türkei